Pengaruh Kualitas Produk Terhadap Kepuasan Sebagai Variabel Intervening (Pada Mahasiswa UnHar Pelanggan Marketplace Online) - Mugi Widya Ningsih; Bagus Handoko; Rizky Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine whether or not there is an effect of product quality, ease of transaction, and product price on repurchase intention with satisfaction as an intervening variable. The total population in this study was 764 people with a specified sample of 100 people, because not all of them used the online marketplace using the Convience Sampling technique. The analytical method used is path analysis of hypothesis testing using the coefficient of determination (R2), simultaneous test (F test), and partial test (t test), Sobel test with data processing using SPSS 25. While the type of research used in this study is associative with a quantitative approach, the data collection technique used is primary data, namely data collection techniques through questionnaires addressed to respondents, namely University of Harapan Medan students located on Jl. Imam Bonjol No. 35, J A T I, Kec. Medan City. The results show that product quality has a negative and insignificant effect on customer satisfaction. Ease of Transaction has a positive and insignificant effect on Customer Satisfaction. Product price has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on repurchase intention. Ease of Transactions has a positive and insignificant effect on repurchase intention. Product price has a positive and insignificant effect on repurchase intention. Customer satisfaction has a positive and significant effect on repurchase interest. Customer satisfaction is not able to mediate product quality on repurchase intention. Customer satisfaction is able to mediate the ease of transactions on the intention to repurchase. Customer satisfaction is able to mediate product price on repurchase intention.